Job Stress in Marketing Executives of Selected Private Sector Banks in Chennai: An Empirical Study - N. V. Ramachandran; Dr. R. Rajendran (International Journal of Management Studies (IJMS), 2021)
Employees are the most important source multipliers particularly for the banking industry. Due to the various developments influencing survival and success of banking executives in marketing, it has become more and more essential to promote their effectiveness with least stress. This study concentrates on the extent to which employees have control over their work, in adequate supervisory support, difficulty in job execution, lack of role clarity and excess work, role intrusion, role deviation and expansion, low self esteem, job in security and poor planning inadequate authority, inefficient work load, high demand and expectation from management, unreachable supervisors, stagnant role, role cut-off and self –role negligence. The primary data was collected from 120 respondents from private bank marketing executives through a structured, tested questionnaire. The findings would be useful to the private banks and their marketing executives in precluding various job stress sources.